Nilai-Nilai Pendidikan Karakter Siswa dalam Program Pembinaan Tahfidzul Qur’an di MI Mu’awanah Banjarwati - Karomah, Wardatul; Ningtias, Ratih Kusuma; Adzimah, Iflahatul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
Character education is the spirit of education because character education can form a whole person. This research aims to determine the implementation of the tahfidzul qur'an development program, the values ​​of character education in the tahfidzul qur'an education program and the obstacles to solutions to implementing the tahfidzul quran development program in fostering character education values ​​in MI Mu'awanah Banjarwati students. This research method is field research which is descriptive qualitative in nature with a case study approach. The tahfidzul Qur'an program is a program for memorizing the words of the Qur'an and their meanings and being able to pronounce them by heart without looking at the mushaf. The results of the research show that the tahfidzul Qur'an coaching program was implemented in five stages, namely: class placement selection, Tahsin, Deposit, Muroja'ah and final exam. The tahfidzul Qur'an development program at MI Mu'awanah Banjarwati has implications for the values ​​of student character education, namely the shiddiq (honest) attitude shown by children by honestly admitting their memorization abilities, fathonah (intelligence) shown by children's intelligence in allocating time to memorize with other activities at school and the attitude of al-Amanah, (it is believed) is shown by children who are enthusiastic and have a firm attitude in memorizing under any circumstances so that when depositing the memorization they can recite it well and correctly without looking at the mushaf. In this case, of course the instilling of character education values ​​of honesty, intelligence and trustworthiness must be carried out in students' daily lives both at school, at home and in the social environment. So that these character values ​​will produce a generation that is always honest in every word and deed, has high intelligence and can always be trusted in carrying out their mandate.